Perbedaan Angka Kejadian Antara Anak Status Gizi Baik dan Gizi Kurang dengan Kejadian Demam Berdarah Dengue di RSUD Kota Surakarta - Prihatiningrum, Reza Meilianie, Dr. Mohammad Wildan, Sp.A (2017)
the incidence of Dengue Hemorrhagic Fever increased sharply all around the world in the last few decades. The incidence rate of Dengue Hemorrhagic Fever in the province of Central Java January 1 - June 30 2016 period was 15.81/100.000 inhabitant with the highest incidence rate was in Surakarta with 57,1. The purpose of this research is to get the specific proportion between incidence of Dengue Hemorrhagic Fever in children with good nutrition and malnutrition. The methods of this research is descriptive analytic research with Cross Sectional research design. The sample is taken using purposive sampling technique. Total sample of this research analyzed using SPSS 23.0 for windows programme. Based on Chi-Square test showed the number of significancy in this research is 0,812 (P>0,05). There are no difference between the number of children with good nutrition and malnutrition with incidence of Dengue Hemorrhagic Fever in Surakarta hospital.